الجزية في واقعنا المعاصر : شبهات فكرية و إشكالات تطبيقية - قويدر، عبدالله عبدالقادر; الخلايلة، أنس محمد عوض (عبد الفتاح محمود ادريس, 2013)
يعتبر تشريع الجزية في الإسلام متوافقاً مع مقاصد التشريع الكلية بشكل عام، ومع مقاصد الجهاد بشكل خاص، كونها تعتبر نتيجة يصل إليها الجهاد في بعض حالاته، ومن ثم كانت الجزية محددة الغاية والمقصد في الشريعة، وهي في حقيقتها ومضمونها لا تمثل أي معنى من معاني الاحتقار أو الإذلال لغير المسلمين في الدولة الإسلامية، بل هي في الحقيقة وسيلة لتحقيق الصورة الكاملة لحق مواطنة غير المسلمين في الدولة الإسلامية، بما يحقق المساواة الكاملة بينهم وبين المسلمين فيها، من خلال فرض واجب مالي يحقق معنى الانتماء للدولة على الشكل الذي لا يؤدي إلى الإضرار بحرية المواطن في الاعتقاد. وكذا لا يوجد شرعاً ما يحتم التمسك باسم الجزية، ولا حصرها بمبلغ أو شكل معين، وبالتالي فهو لا يمثل أي عائق أمام تطبيق هذا الحكم من الناحية الشرعية إن كان هناك حساسية معينة تجاه ذلك. كما توصل البحث إلى عدم صحة ما ينسج حول هذا التشريع من أوهام وصور مشوهة تمس كرامة المواطن غير المسلم في الدولة الإسلامية، بل إن الشريعة تعتبر مثل ذلك مخالفة شرعية تنكرها الشريعة، وترفضها رفضاً تاماً. Legislation jizyah in Islam is compatible with the purposes of the legislation, the college in general and purposes of Jihad in particular and The result reached by the jihad in some cases the jizyah Specific purpose and destination in Islamic law It is, in fact, does not represent any sense of the meaning of humiliation or contempt for non-Muslims in the Islamic state It is in fact a way to achieve the full picture of the right of citizenship to non-Muslims in an Islamic state in order to achieve full equality between them and the Muslims in the state Through the imposition of a duty to achieve financial sense of belonging to the state On the form that does not cause harm to the freedom of the belief in the citizen. As well as the no - in Islamic law - is forced to stick to the name of tribute, not restrict a specific amount or a certain form, if some people have a certain sensitivity towards this name. The researcher found lack of health weaves about this islamic legislation from delusions and distorted images that affect the dignity of the non-Muslims citizens in an Islamic state, the Islamic sharia law flatly rejected.
Keywords: الدولة الإسلامية -- الشريعة الإسلامية -- أهل الذمة -- الجزية -- العصر الحديث